The Development of a New Kinetic Spectrophotometric Method for the Determination of Vanadium(V) Based on its Catalytic Effect on the Oxidation of Malachite Green Oxalate by Bromate in Acidic and Micellar Medium - M. Keyvanfard; N. Abedi (E-Journal of Chemistry)
A new, simple, sensitive and selective kinetic spectrophotometric method was developed for the determination of ultra trace amounts of vanadium(V). The method is based on the catalytic effect of vanadium(V) on the oxidation of malachite green oxalate (MG) by bromate in acidic and micellar medium. The reaction was monitored spectrophotometrically by measuring the decrease in the absorbance of malachite green oxalate (MG) at 625 nm with a fixed-time method. The decrease in the absorbance of MG is proportional to the concentration of vanadium(V) in the range of 1-100 ng/mL with a fixed time of 0.5-2 min from the initiation of the reaction. The limit of detection is 0.71 ng/mL of vanadium(V). The relative standard deviation for the determination of 5, 30, 50 ng/mL of vanadium(V) was2.5% 2.6%, 2.4% and respectively. The method was applied to the determination of vanadium(V) in water samples.